MAPPING DEEP LEARNING TRAJECTORIES THROUGH CHILDREN'S LITERATURE IN CAMBRIDGE TEXTBOOKS - Lubna Iasya; Rahmat Setiawan; Eliasanti Agustina (IJEE (Indonesian Journal of English Education), 2026)
In many English classrooms, textbook-based instruction prioritizes vocabulary retention and grammatical accuracy, often limiting opportunities for deeper cognitive engagement. Although children’s literature is increasingly integrated into English language textbooks, limited research has systematically examined how such materials facilitate the deep learning process, particularly within the framework of deep learning approaches proposed by Ference Marton and Roger Saljo (1976). This qualitative case study investigates how children’s literary texts and accompanying instructional tasks in twelve Cambridge English textbooks support deep learning in the Indonesian EFL context. Data were collected through document analysis of seventy literary texts and their instructional sequences, complemented by semi-structured interviews with teachers. The findings reveal a four-stage pedagogical trajectory consisting of contextual meaning-making, interpretative analysis, language application, and creative transfer. Teachers also perceived literature as an effective resource for supporting higher-order thinking and contextualized learning. By conceptualizing deep learning as a structured pedagogy trajectory rather than a static outcome, this study contributes to literature-based pedagogy research and offers implications for textbook design and instructional practice.